Domestic Waste Generation and Management During COVID-19 in Tambahrejo Village - Larasati; Prehatin Trirahayu Ningrum; Anita Dewi Moelyaningrum; Yudhiakuari Sincihu (Indonesian Journal of Administration and Health Research (IJAHR), 2025)
Villages in Candipuro District, Lumajang Regency, including Tambahrejo Village, have not implemented programs in cooperation with the Environmental Agency for household waste collection, both before and during the Covid-19 pandemic. According to Regional Regulation No. 58 of 2018, Lumajang Regency targeted a 26% reduction and 73% handling of household waste by 2022. This study analyzed household waste production, composition, and management during the pandemic to support JAKSTRADA policy. The study used a descriptive observational method with a cross-sectional design, measuring waste according to SNI 19-3964-1994, interviews, and observation. Results showed an average household waste weight of 0.32 kg/person/day and a volume of 3.42 liters/person/day. Potential waste from households with members engaging in home learning reached 168,101.32 kg/day, dominated by 46.11% organic waste. Waste reduction and processing reached 4.72% and 4.7%. Domestic waste increased during the pandemic, while management remained suboptimal. Recommended strategies include source-based waste separation, optimization of waste banks, application of the 3R principle, continuous community education, and collaboration between village authorities, schools, and residents to improve the effectiveness of domestic waste management.